Genetic diversity, phylogeography, population structure, and demographic history of wild Catla catla at a transboundary scale across South Asia revealed by Mitochondrial COI sequences - J. K. Owaresat; Diptta Dey; Md. Ahashan Habib Siam; Md. Ashraful Anam; Ammam Zonaed Siddiki (PLoS ONE, 2026)
This study presents the first assessment of mitochondrial cytochrome c oxidase I (COI) sequences from multiple countries to evaluate the genetic diversity, phylogeographic relationships, population structure, and demographic history of wild Catla catla in South Asia. A total of 18 haplotypes, with moderate haplotype diversity (Hd = 0.599), low nucleotide diversity (π = 0.017), and limited mutational steps among most haplotypes, were identified after analyzing 133 COI sequences collected from Bangladesh, India, and Pakistan. The results revealed low genetic differentiation among all wild Catla samples, influenced by introgression from hatchery-reared fry and population bottlenecks. Phylogenetic analyses identified two distinct haplogroups for Pakistani populations, supporting the existence of divergent mitochondrial lineages. AMOVA test showed that most genetic variation occurred within populations (74.46.%) rather than among the seven river basin populations (25.54%). The high pairwise genetic distance (FST= 0.255), together with the presence of numerous population-specific haplotypes and low gene flow (Nm = 0.729), indicated significant population structure among these river populations. A positive Mantel test (r = 0.12) confirmed a significant increase in genetic divergence with increasing geographic distance. The neutrality test and mismatch distribution presented a contrasting demographic history. A significantly negative Fu’s Fs (Fu’s Fs = −24.431) pointed to recent population expansion, whereas a significant Harpending’s raggedness index (r = 0.009) and a multimodal mismatch distribution suggested long-term demographic substructure. These findings provide essential COI-based baseline genetic information for conserving the genetic integrity of the wild Catla catla and guiding sustainable transboundary fisheries management in South Asia.